Advertising Design Influence on Promotion Strategies and Consumer Purchasing Decisions - Fadilla, M F; Sya’roni, D A W (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Advertising design influence on promotion strategies and consumer Purchasing Desiaions is a significant factor in marketing. This study employed a descriptive qualitative research method to analyze the extent of advertising design influence on promotions strategies and consumer purchasing decisions. The data collection process was conducted in two stages, which included observation to gather data from existing cases and a literature study to strengthen research results with theory and previous research. The results of the study indicated that advertising design in promotions plays a crucial role in influencing consumer purchasing decisions. This is because advertising serves as a promotional component, providing a source of information that can build trust in products and brands. The findings of the study suggest that advertisement design as a source of information must be designed to build consumer trust so that a purchase occurs. A well-designed advertisement can help create a positive image of a brand or product in the minds of consumers, leading to increased trust in the brand and higher chances of making a purchase. This highlights the importance of investing in effective advertising design to achieve marketing objectives. Overall, this study provides valuable insights into the significance of advertising design in promotions and its impact on consumer purchasing decisions. It emphasizes the importance of carefully designing advertisements to build consumer trust, thereby achieving marketing objectives. The research findings can be used to guide marketing efforts and help businesses create effective advertising campaigns that deliver results.